Overview of CGIAR Climate Change, Agriculture and Food Security Research Program (CCAFS) - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Presentation to the Chinese Academy of Agricultural Sciences (CAAS) on 16 October 2018, Beijing, China